UJI EFEKTIVITAS BIOPESTISIDA TEMBAKAU TERHADAP SERANGAN HAMA THRIPS (Thrips tabaci Lidenam) PADA PERTUMBUHAN PUCUK TANAMAN TEH (Camellia sinensis) - Kris Julianto; Tyas Soemarah Kurnia Dewi; Endang Suprapti; Dwi Susilo Utami; Haryuni Haryuni (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2022)
Tea (Camellia sinensis Lidenam.) is a plant whose shoots are taken for a beverage. Tea plants are susceptible to attack by Plant Pest Organisms (OPT) which have the potential to reduce yields by up to 30%, in severe attacks can reduce production by up to 50%. The purpose of this study was to determine the effect of tobacco biopesticide treatment on the intensity of attack and the percentage of pest attack (Thrips tabaci lidenam) on the shoots of tea plants. The study was carried out at PT Rumpun Sari Kemuning in Kemuning, Ngargoyoso, Karanganyar, on April 1 - June 29, 2021. This study used a Completely Randomized Block Design method with 6 treatments and 4 replications. The first treatment was J0: Control, J1: 0.05% Biopesticide Concentration, J2: 0.1% Biopesticide Concentration, J3: 0.15% Biopesticide Concentration, J4: 0.20% Biopesticide Concentration, J5: 0.25 Biopesticide Concentration %, the biopesticide treatment was carried out 12 times. The results of this study showed that the use of tobacco biopesticide 0.20% gave the best results against the percentage of pest attacks, namely 40.00%. And the use of 0.25% biopesticide gave the best results against the percentage of pest attack intensity of 8.75%.